Teachers’ Perception Towards Curriculum Change in Indonesia - Adriani Putri Hura (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Teachers' perceptions of changes to the curriculum are something interesting in language. The study aims to describe the perception of teachers on curriculum change in Indonesia. This research was conducted using qualitative methods in Gunungsitoli city, North Sumatra province. This research involved several teachers from various schools in Gunungsitoli city. Data collection was carried out through interviews by asking several questions about teachers' perceptions of curriculum changes.